Effect of the addition of potassium and magnesium ions on the thermal, pasting, and functional properties of plantain starch (Musa paradisiaca) - Mutis González, Nathalia; Pineda Gómez, Posidia; Rodríguez García, Mario Enrique (International journal of biological macromolecules, 2019)
Starch is a biopolymer widely used in the industry; however, rarely used in its native form, making necessary its modification. This work studied the effect of the inclusion of potassium and magnesium ions on the physicochemical properties of plantain starch. Ionic solutions were prepared at five concentrations between 0.0 and 0.3 M. The gelatinization, thermal degradation, viscosity, swelling power, morphological and structural changes were studied. Results showed that ion addition increased the swelling and solubility index. Both ions affected the gelatinization temperature; shift in characteristic temperatures was observed. The more significant change in the viscosity profile was showed in the final region; both ions permitted the re-ordering of the polymeric chains, but magnesium showed a greater trend towards viscosity recovery. In the thermogravimetric analysis, a lower degradation temperature was observed for starch added with ions. Structural analysis showed that for higher concentrations of potassium the addition was not carried out and crystallographic phase potassium chloride appears in the diffractogram. All the results showed that the ions inclusion produced changes in the physicochemical properties on starch, but magnesium had a greater effect on its polymeric matrix according to infrared spectroscopy, which could be due to its high electronegativity and low molecular weight. •The presence of ions in the plantain starch slows down the gelatinization transition.•Ion inclusion favors the viscosity recovery during cooling.•Plantain starch added with ions degrades at lower temperatures.•Plantain starch added with magnesium showed the greater changes for all the properties analyzed.